2018
DOI: 10.1016/j.jcis.2017.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of a new carboxylated cellulose derivative. Part III: Removal of auramine-O and safranin-T from mono- and bi-component spiked aqueous solutions

Abstract: In the third part of this series of studies, the adsorption of the basic textile dyes auramine-O (AO) and safranin-T (ST) on a carboxylated cellulose derivative (CTA) were evaluated in mono- and bi-component spiked aqueous solutions. Adsorption studies were developed as a function of solution pH, contact time, and initial dye concentration. Adsorption kinetic data were modeled by monocomponent kinetic models of pseudo-first- (PFO), pseudo-second-order (PSO), intraparticle diffusion, and Boyd, while the competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…However, their lack of thermo-plasticity, poor dimensional stability and poor crease-resistance retard their adsorption performance properties [23]. These properties can be improved by subjecting the cellulosic fabric to different chemical modifications for example grafting of different monomers to the cellulosic chain or etherification reaction [24][25][26][27][28][29][30][31][32]. Other performance properties, like thermal stability and resistance to biological and chemical agents, can also be improved through chemical modification and consequently applied as an absorbent in wastewater purification [33][34][35][36][37][38], ion-exchangers for the removal of metal cations from aqueous solutions [39][40][41][42][43][44], etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, their lack of thermo-plasticity, poor dimensional stability and poor crease-resistance retard their adsorption performance properties [23]. These properties can be improved by subjecting the cellulosic fabric to different chemical modifications for example grafting of different monomers to the cellulosic chain or etherification reaction [24][25][26][27][28][29][30][31][32]. Other performance properties, like thermal stability and resistance to biological and chemical agents, can also be improved through chemical modification and consequently applied as an absorbent in wastewater purification [33][34][35][36][37][38], ion-exchangers for the removal of metal cations from aqueous solutions [39][40][41][42][43][44], etc.…”
Section: Introductionmentioning
confidence: 99%
“…4 Auramine-O is a basic dye that is used to dye wool, silk, acrylic bers, and leather in the textile industries; however its presence in water source causes acute oral toxicity, carcinogenicity, cytotoxicity, DNA damage, genotoxicity, and mutagenicity. 5 Furthermore, triphenylmethane dyes, which are used as colorants and antimicrobial agents in diverse industries, are also known as organic water pollutants. 6 Triphenylmethane dyes are used extensively in the textile industry for dyeing nylon, wool, cotton, and silk, as well as for coloring oil, fats, waxes, varnish, and plastics.…”
Section: Introductionmentioning
confidence: 99%
“…33 Investigations have revealed that metallic Ag could improve the transfer capability of photo-generated electron-hole pairs of the Ag 3 PO 4 / BiVO 4 composite. 34 Furthermore, investigations indicated that metallic Ag has an undeniable role in the charge separation promotion and photoactivity enhancement for the construction of ternary heterojunctions including Ag@g-C 3 N 4 @BiVO 4 [5] 37 These heterojunction photocatalysts enhance the photo-excited carrier separation related to the undeniable role of Ag, which can induce localized surface plasmon resonance. Consequently, these Ag-Bi-based photocatalysts not only improve the rate of the electron-hole pair generation but also expand the visible light-responsive range.…”
Section: Introductionmentioning
confidence: 99%
“…Safranine T (ST), a typical kind of cationic azine dye, is one of the most commonly used organic dyes. ST is widely used as textile colorant for dyeing tannin, cotton, bast fibers, wool, silk, leather, and paper [23,24]. Therefore, ST was chosen to study the adsorption properties of MR–FeS@SC nanocomposite.…”
Section: Introductionmentioning
confidence: 99%